Hypoglycaemia in severe malaria, clinical associations and relationship to quinine dosage - Ogetii, Gilbert N (BioMed Central, 2010)
BACKGROUND: Hypoglycaemia is an independent risk factor for death in severe malaria and a recognized adverse treatment effect of parenteral quinine. In 2006 our hospital changed quinine treatment policy from 15 mg/kg loading (plus 10 mg/kg 12-hourly) to 20 mg/kg loading (plus 10 mg/kg 8-hourly) to comply with new WHO guidelines. This presented us with the opportunity to examine whether there was any dose relationship of quinine and hypoglycaemia occurrence. METHODS: Retrospective case notes review of all children admitted to hospital with severe falciparum malaria between April 2002 - July 2009, before and after the introduction of the new WHO quinine regimen. Four-hourly bedside glucose levels were measured until intravenous quinine was discontinued. Clinical events immediately preceding or concurrent with each episode of hypoglycaemia (glucose < = 3.0 mmol/l) were recorded. RESULTS: 954 children received the old quinine regime and 283 received the new regime. We found no evidence of an increased prevalence of hypoglycaemia (< = 3.0 mmol/L) on the new regime compared to former (15% vs. 15%); similar findings were noted for profound hypoglycaemia (< 2.2 mmols/L) 8% v 5%, P = 0.07. Episodes were co-incident with disease severity markers: coma (57%), circulatory failure (38%) and respiratory distress (21%) but less commonly with seizures (10%). Disruption of maintenance fluids and/or blood transfusion concurred with 42% of the hypoglycaemia episodes. Post admission hypoglycaemia increased odds of fatal outcome (24%) compared to euglycaemic counterparts (8%), odds ratio = 3.45 (95% confidence interval = 2.30-5.16) P < 0.01. CONCLUSION: There was no evidence to indicate a dose relationship between quinine and occurrence of hypoglycaemia. Hypoglycaemia concurred with severity features, disruption of glucose infusion and transfusion. Careful glucose monitoring should be targeted to these complications where resources are limited.